IJANR 2021
DOI: 10.7764/ijanr.v48i2.2269
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of macronutrients and productivity of potato with foliar application of biofertilizer

Abstract: The addition of organic compounds to fertilizers has shown positive effects on plant metabolism. This study aimed to evaluate the macronutrient accumulation and productivity of potato with the use of biofertilizer (BF) applied to the leaves. A 2×7 factorial plot with a plot subdivided in time and ten replications used two forms of fertilization: a chemical fertilizer with conventional NPK (nitrogen, phosphorus and potassium: control) and conventional fertilizer plus biofertilizers (BF); evaluations were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
0
0
Order By: Relevance
“…Satoru (Ishikawa et al, 2011) studied the Cd dynamic curves of Japonica rice varieties with low Cd content and Indica rice varieties with high Cd content and found that the root of Japonica rice varieties with low Cd content had a higher capacity for Cd absorption. Similar results were observed in studies comparing Cd accumulation among varieties of potato (Gonçalves et al, 2009;Moghadam and Shahmoradi, 2021;Pinheiro-Araújo et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Satoru (Ishikawa et al, 2011) studied the Cd dynamic curves of Japonica rice varieties with low Cd content and Indica rice varieties with high Cd content and found that the root of Japonica rice varieties with low Cd content had a higher capacity for Cd absorption. Similar results were observed in studies comparing Cd accumulation among varieties of potato (Gonçalves et al, 2009;Moghadam and Shahmoradi, 2021;Pinheiro-Araújo et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Alongside evaluating potato plant growth and yield, an indicator commonly used to gauge the influence of biofertilizers on the macro and micronutrient contents was essential for the potato's lifecycle [54]. This assessment revealed significant variations in the levels of these nutrients due to the different biofertilizers examined in this study.…”
Section: Discussionmentioning
confidence: 88%
“…Nitrate reductase activity is heightened, leading to better nutrient utilization, and the biofertilizers even play a role in producing compounds that act against pathogens [32]. Araújo et al [54] and Sharma and Pandey [55] reported that applying biofertilizers in conjunction with mineral fertilizers significantly influenced the marketable tuber yield of potatoes compared to untreated plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation